CSF and blood biomarkers for the diagnosis of Alzheimer's disease: a systematic review and meta-analysis. Issue 7 (June 2016) - Olsson, Bob; Lautner, Ronald; Andreasson, Ulf; Öhrfelt, Annika; Portelius, Erik; Bjerke, Maria; Hölttä, Mikko; Rosén, Christoffer; Olsson, Caroline; Strobel, Gabrielle; Wu, Elizabeth; Dakin, Kelly; et al.
Summary: Background: Alzheimer's disease biomarkers are important for early diagnosis in routine clinical practice and research. Three core CSF biomarkers for the diagnosis of Alzheimer's disease (Aβ42, T-tau, and P-tau) have been assessed in numerous studies, and several other Alzheimer's disease markers are emerging in the literature. However, there have been no comprehensive meta-analyses of their diagnostic performance. We systematically reviewed the literature for 15 biomarkers in both CSF and blood to assess which of these were most altered in Alzheimer's disease. Methods: In this systematic review and meta-analysis, we screened PubMed and Web of Science for articles published between July 1, 1984, and June 30, 2014, about CSF and blood biomarkers reflecting neurodegeneration (T-tau, NFL, NSE, VLP-1, and HFABP), APP metabolism (Aβ42, Aβ40, Aβ38, sAPPα, and sAPPβ), tangle pathology (P-tau), blood–brain-barrier function (albumin ratio), and glial activation (YKL-40, MCP-1, and GFAP). Data were taken from cross-sectional cohort studies as well as from baseline measurements in longitudinal studies with clinical follow-up. Articles were excluded if they did not contain a cohort with Alzheimer's disease and a control cohort, or a cohort with mild cognitive impairment due to Alzheimer's disease and a stable mild cognitive impairment cohort. Data were extracted by ten authors and checked by two for accuracy. For quality assessment, modified QUADAS criteria were used. Biomarker performance was rated by random-effects meta-analysis based on the ratio between biomarker concentration in patients with Alzheimer's disease and controls (fold change) or the ratio between biomarker concentration in those with mild cognitive impariment due to Alzheimer's disease and those with stable mild cognitive impairment who had a follow-up time of at least 2 years and no further cognitive decline. Findings: Of 4521 records identified from PubMed and 624 from Web of Science, 231 articles comprising 15 699 patients with Alzheimer's disease and 13 018 controls were included in this analysis. The core biomarkers differentiated Alzheimer's disease from controls with good performance: CSF T-tau (average ratio 2·54, 95% CI 2·44–2·64, p<0·0001), P-tau (1·88, 1·79–1·97, p<0·0001), and Aβ42 (0·56, 0·55–0·58, p<0·0001). Differentiation between cohorts with mild cognitive impairment due to Alzheimer's disease and those with stable mild cognitive impairment was also strong (average ratio 0·67 for CSF Aβ42, 1·72 for P-tau, and 1·76 for T-tau). Furthermore, CSF NFL (2·35, 1·90–2·91, p<0·0001) and plasma T-tau (1·95, 1·12–3·38, p=0·02) had large effect sizes when differentiating between controls and patients with Alzheimer's disease, whereas those of CSF NSE, VLP-1, HFABP, and YKL-40 were moderate (average ratios 1·28–1·47). Other assessed biomarkers had only marginal effect sizes or did not differentiate between control and patient samples. Interpretation: The core CSF biomarkers of neurodegeneration (T-tau, P-tau, and Aβ42), CSF NFL, and plasma T-tau were strongly associated with Alzheimer's disease and the core biomarkers were strongly associated with mild cognitive impairment due to Alzheimer's disease. Emerging CSF biomarkers NSE, VLP-1, HFABP, and YKL-40 were moderately associated with Alzheimer's disease, whereas plasma Aβ42 and Aβ40 were not. Due to their consistency, T-tau, P-tau, Aβ42, and NFL in CSF should be used in clinical practice and clinical research. Funding: Swedish Research Council, Swedish State Support for Clinical Research, Alzheimer's Association, Knut and Alice Wallenberg Foundation, Torsten Söderberg Foundation, Alzheimer Foundation (Sweden), European Research Council, and Biomedical Research Forum.